Synthesis and physical and biological properties of 1, 3-diaza-2-oxophenoxazine-conjugated oligonucleotides. (15th October 2022) - Yamaji, Ryohei; Nakagawa, Osamu; Kishimoto, Yuki; Fujii, Akane; Matsumura, Tomoki; Nakayama, Taisuke; Kamada, Haruhiko; Osawa, Takashi; Yamaguchi, Takao; Obika, Satoshi
Graphical abstract: Abstract: The artificial nucleobase 1, 3-diaza-2-oxophenoxazine (tC O ) and its derivative G-clamp strongly bind to guanine and, when incorporated into double-stranded DNA, significantly increase the stability of the latter. As the phenoxazine skeleton is a constituent of major pharmaceuticals, we hypothesized that oligonucleotides (ONs) containing phenoxazine bases would induce property changes related to intracellular uptake and migration in tissues. In this study, we designed and synthesized a novel G-clamp-linker antisense oligonucleotide (ASO) in which a G-clamp base with a flexible linker was introduced into the 5′-end of an ASO targeting mouse long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (m MALAT1 ). Compared to unconjugated ASO, the G-clamp-linker ASO induced significantly more effective knockdown of m MALAT1 in mouse skeletal muscle. The ASOs conjugated with 2′-deoxyribonucleotide(s) bearing a tC O nucleobase at the 5′-end exhibited a similar knockdown effect in skeletal muscle. Thus, it may be possible to improve therapeutic effects against skeletal muscle diseases, such as muscular dystrophy, by using ONs with incorporated phenoxazine nucleobases.